Energy Transition, Environmental Sustainability and Healthcare Costs in Emerging Sub-Saharan Economies: Evidence from the Pre- and During-COVID-19 Periods – Implications for SDG 3, SDG 7 and SDG 13 - Xu, Changhong; Xu, Changhua (Problemy Ekorozwoju, 2026)
This study investigates the interconnections between energy transition, environmental sustainability, and healthcare costs in emerging Sub-Saharan African (SSA) economies, with a specific focus on their implications for Sustainable Development Goals (SDGs) 3 (Good Health and Well-being), 7 (Affordable and Clean Energy), and 13 (Climate Action). Employing a strongly balanced panel dataset of 40 SSA countries spanning 2005 to 2020, the analysis integrates Energy Transition Theory and Grossman’s Health Production Model to evaluate how shifts in energy systems, environmental conditions, and healthcare financing affect sustainable development outcomes. Using panel estimation techniques, four interrelated econometric models examine the determinants of environmental sustainability, the impact of environmental quality and energy use on healthcare costs, the influence of health financing on outcomes, and the drivers of clean energy access. The results reveal significant regional disparities. Renewable energy consumption positively influences environmental sustainability in Central and East Africa but exhibits a negative effect in Southern Africa. GDP per capita is negatively associated with environmental quality across all regions, consistent with early-stage environmental Kuznets curve dynamics. Clean energy consumption is associated with lower healthcare expenditure, while public health spending has a more consistent positive effect on health outcomes than private spending. COVID-19 dynamics significantly altered these relationships. The pandemic weakened the previously strong link between renewable energy and environmental sustainability and intensified the negative association between GDP and environmental outcomes, particularly in West Africa. For healthcare outcomes, pre-pandemic patterns of effective public investment and economic growth were disrupted, as emergency responses and resource reallocation diluted long-term structural relationships. The contribution of GDP per capita to SDG 7 remained robust, even during the pandemic, reaffirming the foundational role of economic strength in driving energy transitions. However, the synergies between SDG 7 and SDG 13 weakened in most regions, with Southern Africa standing out for maintaining and even strengthening these interlinkages under crisis conditions. Demographic factors, such as population age, also exhibited regionally specific effects, particularly in Southern Africa, where they remained significant throughout the pandemic. These findings demonstrate the importance of regionally tailored and resilient policy strategies. Governments should prioritise clean energy investments, not only for environmental benefits but also to reduce healthcare burdens. Post-pandemic recovery plans must integrate green fiscal reforms and re-anchor health systems on principles of equity, resilience, and efficiency. The Southern African experience offers a potential blueprint for policy continuity and SDG alignment during future crises. Overall, the research points to the need for coordinated, cross-sectoral interventions to accelerate sustainable development in Sub-Saharan Africa, particularly in the face of global shocks.